Kenaikan Harga Bahan Bakar Minyak (Bbm) Atas Nama Rakyat (Tinjauan Kritis Konsepsi Keadilan Sosial Ekonomi Ibnu Taimiyah) - Arin Setiyowati (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2019)
AbstractThe continue phenomenon of fuel prices increasing in Indonesia arealways both between the two sides (there are government andcommunity). Debating the agree side and disagree side of being the maincontents of the escort policies. But we know the socio-economicscondition of ‘tragic’ Indonesia be raised expenditures greater thanrevenues, while expenditure was only focused on subsidies ofenergywhich unfortunatelymore widely used by the upper middle classsociety rather than small communities. Besides external factors that affectthe pattern of the domestic politics of oil policy. In the position of theeconomic dilemma, the government apllying the economic logic of "ParetoOptimum ", it’s meanthat the transfering of enjoyment to be fair, but it isn’tonly focusing only on short-term policies, but also followed byreconstruction the quality of sustainable development. And Ibn Taimiyyahas one of the Islamic Economic Thinkers, which one of the legacyof thesocio- economicjustice concept to be analysis study and be the counter ofthe phenomenon of rising fuel prices and Compensation Package, as wellas to macroeconomic conditions in Indonesia.Keywords : Oil Politics, the rising prices of fuel and fuel subsidies, fuelcompensation package, The Conception of Socio-Economic Justice fromIbn Taimiyyah.